Design and testing of a trap removing Chinese mitten crabs (Eriocheir sinensis, H. Milne Edwards, 1853) from invaded river systems. (21st April 2020) - Schoelynck, Jonas; Van Loon, Paul; Heirmans, Ritchie; Jacobs, Steven; Keirsebelik, Heleen
Abstract: The Chinese mitten crab is one of the top invasive species in Europe. In Flanders (Belgium), they are associated with river ecosystem degradation, especially the loss of aquatic vegetation and associated ecosystem services. Management measures have therefore been put in place to reduce the number of crabs migrating between the sea and freshwater areas and ultimately control the population. Although we are still long way from the goal, a low‐cost method has been applied to successfully catch migrating crabs. In this article, we outline the design and functioning of the trap. We monitored the population in a lowland river, measured migration speeds and calculated crab densities. With over 1 million crabs caught in 2 years, the trap proved to be very effective. Median anadromous (spring) and catadromous (autumn) migration speeds were 0.69 and 0.96 km day −1, respectively. Anadromous migrating crab density was calculated to be up to 3.20 ind. m −2 river bed. Resident crab density was calculated to be up to 2.05 ind. m −2 river bed. We conclude that this trap is a very useful tool for water managers to catch Chinese mitten crabs in rivers and discuss the pathways towards reducing the population and protect the entire freshwater catchment.